Determinación de TGO. TGP, fosfatasa alcalina bilirrubinas y proteínas totales en pacientes internados en tres centros psicoteraupeuticos de la ciudad de Machala en el año 2008 - Campoverde Leon, Joseph D. (2009)
The alcoholism is a social disease that increasingly charged more force with the passage of time are more people that fall into the abyss of the many times it is very difficult to quit, since this a disease slowly begins when the person in giving the first sings of his taste or his inclination towards alcohol consumption since as said previously the person looking for a shelter or aid species either by problems or situations of different nature affecting the person what not you realize is that are falling into another problem worse still is one disease that a will son deteriorate the person not only in its physical appearance but also his body that then leads fatal outcomes as death.